2001
DOI: 10.1055/s-2001-13687
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Nitrates onto the Papilla of Vater: Manometric and Clinical Results

Abstract: Both topically administered GTN and ISDN evoked a profound inhibition of SO motility, but the effect of ISDN was longer lasting than that of GTN. However, locally administered GTN did not facilitate selective bile-duct access during routine ERCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…5 Systemic or sublingual administration of glyceryl trinitrate also relaxes the sphincter of Oddi. 6 Although neither drug when sprayed on the papilla decreases the incidence of post-ERCP pancreatitis, 5,6 there is a need to investigate other agents that effectively reduce the rate of this common and potentially severe complication.…”
Section: Introductionmentioning
confidence: 99%
“…5 Systemic or sublingual administration of glyceryl trinitrate also relaxes the sphincter of Oddi. 6 Although neither drug when sprayed on the papilla decreases the incidence of post-ERCP pancreatitis, 5,6 there is a need to investigate other agents that effectively reduce the rate of this common and potentially severe complication.…”
Section: Introductionmentioning
confidence: 99%
“…Ghori et al [9] administered sublingual GTN (400-800 lg) prior to ERCP and demonstrated an overall improvement in cannulation rate but not in the time to cannulation. Wehrmann et al [25] used topical GTN and were unable to demonstrate any advantageous effect on the number of cannulation attempts or time to successful cannulation. The rates of NKP in the two groups in their study were not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of GTN wane after 2-3 min [15,25]. As is often the case, the more difficult procedures are likely to involve anatomical variations, thus taking longer to perform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another randomized controlled trial showed that intravenous administration of CCK during ERCP had no effect on cannulation [52] . Topical nitroglycerin was also shown to relax the sphincter of Oddi but there was no effect on rates of selective bile duct cannulation [53,54] .…”
Section: Pharmacologic Methods To Facilitate Cannulationmentioning
confidence: 99%